Vpliv pravokotnosti mreže na konvergenco programa SIMPLE za reševanje Navier-Stokes-ovih enačb - Džijan, Ivo (Strojniški vestnik, 2007)
A finite-volume method for solving the Navier-Stokes equations on a locally orthogonal unstructured grid using the SIMPLE algorithm has been developed. The developed method was compared with a similar method on a structured, not necessarily orthogonal grid, in terms of convergence history and the range of under-relaxation factors in which the methods converge. When the structured grid is orthogonal, the convergence rates of the two methods are similar. For the cases when the structured grid is non-orthogonal, the superiority of the proposed method on the locally orthogonal grid is demonstrated in terms of convergence history. In these cases, the range of under-relaxation factors in which the proposed method shows satisfactory convergence is much wider than for the method on the non-orthogonal grid.
Keywords: Navier-Stokesove enačbe; metoda končnih volumnov; algoritmi; nestrukturirane mreže